2008
DOI: 10.1021/es800577a
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Degradation and Endocrine Disrupting Activity of Nonylphenols

Abstract: Degradation of technical nonylphenol by Sphingobium xenophagum Bayram led to a significant shift in the isomers composition of the mixture. By means of gas chromatography-mass spectrometry, we could observe a strong correlation between transformation of individual isomers and their alpha-substitution pattern, as expressed by their assignment to one of six mass spectrometric groups. As a rule, isomers with less bulkiness at the alpha-carbon and those with an optimally sized main alkyl chain (4-6 carbon atoms) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
107
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 34 publications
11
107
1
Order By: Relevance
“…Proteomic studies of filamentous fungi have only recently begun to appear in the literature, despite the prevalence of these organisms in the fields of biotechnology, industry and environmental protection and their importance as both human and plant pathogens (Kim et al 2007;Doyle 2011;Bregar et al, 2012;Salvachúa et al 2013;Kroll et al 2014). Although the fungal biodegradation pathways of 4-NP have been proposed for several fungal organisms (Junghanns et al 2005;Gabriel et al 2008;Girlanda et al 2009;Różalska et al 2010;Krupiński et al 2013), little is known about the proteomic background of these processes. In the current work, the 4-n-NP biodegradation pathway in the filamentous fungus, Metarhizium robertsii, which leads to the complete removal of the xenobiotic through consecutive oxidations of the alkyl chain followed by aromatic ring oxidation and the initial proteome background of 4-n-NP removal, was described.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic studies of filamentous fungi have only recently begun to appear in the literature, despite the prevalence of these organisms in the fields of biotechnology, industry and environmental protection and their importance as both human and plant pathogens (Kim et al 2007;Doyle 2011;Bregar et al, 2012;Salvachúa et al 2013;Kroll et al 2014). Although the fungal biodegradation pathways of 4-NP have been proposed for several fungal organisms (Junghanns et al 2005;Gabriel et al 2008;Girlanda et al 2009;Różalska et al 2010;Krupiński et al 2013), little is known about the proteomic background of these processes. In the current work, the 4-n-NP biodegradation pathway in the filamentous fungus, Metarhizium robertsii, which leads to the complete removal of the xenobiotic through consecutive oxidations of the alkyl chain followed by aromatic ring oxidation and the initial proteome background of 4-n-NP removal, was described.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater treatment decreases the concentration of NPEs but increases the concentration of the toxic metabolites of NPEs. 67 Use. Studies have found that textiles manufactured in factories that use NPEs frequently contain residual NPEs in the final product.…”
Section: Parts Of the Life Cycle Affectedmentioning
confidence: 99%
“…Nonylphenols are known to disrupt normal endocrine functions in vertebrates (57). Certain isomers contained in t-NP have been reported to possess a considerably higher estrogenic activity than the t-NP mixture (15). Due to increasing concerns with respect to their largely unknown environmental fate and potentially adverse environmental and human health effects, nonylphenols have been listed as priority hazardous substances in the EU water framework directive.…”
mentioning
confidence: 99%
“…Bacterial degradation pathways have only been documented in the genera Sphingomonas and Sphingobium. Bacterial mineralization of the aromatic moiety of t-NP isomers to CO 2 and H 2 O is initiated via ring hydroxylation at the ipso (C-4) position of the phenolic ring, and nonanols are produced from the nonyl chains (10,11,15,16). Bacteria have been shown to utilize branched-chain nonylphenols as growth substrates (11,12,17,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation